2014
DOI: 10.1080/03235408.2013.868696
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness determination of wheat genotypes andStbresistance genes against IranianMycosphaerella graminicolaisolates

Abstract: Septoria tritici blotch (STB) caused by Mycosphaerella graminicola is a serious disease in some wheat-growing regions of Iran. Continuous monitoring of the fungus populations is indispensable to study the efficiency of known resistant cultivars and Stb genes. In this study, resistance of 49 wheat genotypes, including 20 wheat differential cultivars worldwide and 29 other wheat genotypes, were studied to 19 M. graminicola isolates. Among 931 genotype-isolate interactions, 224 isolate-specific resistances (26%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 56 publications
6
13
0
Order By: Relevance
“…Comparing to our previous studies and other reports elsewhere in the world (Eyal et al 1983;Chartrain et al 2004a;Abrinbana et al 2012;Ghaneie et al 2012;Hosseinnezhad et al 2014), the number of specific resistances identified in this study was considerable. Of 150 interactions, 78 isolate-specific interactions (52%) were identified, indicating that SHWs possessed many known or novel effective resistance genes.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Comparing to our previous studies and other reports elsewhere in the world (Eyal et al 1983;Chartrain et al 2004a;Abrinbana et al 2012;Ghaneie et al 2012;Hosseinnezhad et al 2014), the number of specific resistances identified in this study was considerable. Of 150 interactions, 78 isolate-specific interactions (52%) were identified, indicating that SHWs possessed many known or novel effective resistance genes.…”
Section: Discussionsupporting
confidence: 57%
“…; Hosseinnezhad et al. ), the number of specific resistances identified in this study was considerable. Of 150 interactions, 78 isolate‐specific interactions (52%) were identified, indicating that SHWs possessed many known or novel effective resistance genes.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This genotype contains Stb16 and Stb17 (Tabib Ghaffary et al 2012;Mahboubi et al 2020). Therefore, it can be concluded that this gene still is effective against STB, which is consistent with previous (Hosseinnezhad et al 2014;Makhdoomi et al 2015). The resistant genotypes identi ed in this study are likely novel sources of resistance, which can be used in breeding programs for the development of modern wheat cultivars.…”
Section: Discussionsupporting
confidence: 86%